A Subgraph Operator for Graph Transformation Languages - Balasubramanian, Daniel; Narayanan, Anantha; Neema, Sandeep; Shi, Feng; Thibodeaux, Ryan; Karsai, Gabor (Electronic Communications of the EASST, 2007)
In practical applications of graph transformation techniques to model transformations one often has the need for copying, deleting, or moving entire subgraphs that match a certain graph pattern. While this can be done using elementary node and edge operations, the transformation is rather cumbersome to write. To simplify the transformation, we have recently developed a novel approach that allows selecting subgraphs from the matched portion of the host graph, applying a filter condition to the selection, and performing a delete, move, or copy operation on the filtered result in the context of a transformation rule. The approach has been implemented in the GReAT language and tested on examples that show the practical efficacy of the technique. The paper describes the technique in detail and illustrates its use on a real-life example.